1993
DOI: 10.1111/j.1365-2796.1993.tb00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between blood pressure and plasma insulin in acromegaly

Abstract: We conclude that hyperinsulinaemia may be involved in an increase in blood pressure in active acromegalics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Several studies have indicated the existence of a relationship between the GH/IGF‐I axis and the cardiovascular system, hypothesizing a role for GH/IGF‐I in the development of hypertension 1–5 . The GH/IGF‐1 axis regulates plasma volume through renal sodium absorption 6–8 and inhibition of natriuresis, 9 stimulates collagen deposition at the endothelium, so inducing an increase in the intima–media thickness and endothelial dysfunction, 34–36 modifies the circadian activity of the sympathetic system, 37 and regulates glucose metabolism 38,39 . However, IGF‐I also has vasorelaxation and protective effects on the vascular system, inducing nitric oxide 1,2 and elastin synthesis, 40 interacting with vascular smooth cell potassium channels 41 and preventing apoptosis of these cells 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated the existence of a relationship between the GH/IGF‐I axis and the cardiovascular system, hypothesizing a role for GH/IGF‐I in the development of hypertension 1–5 . The GH/IGF‐1 axis regulates plasma volume through renal sodium absorption 6–8 and inhibition of natriuresis, 9 stimulates collagen deposition at the endothelium, so inducing an increase in the intima–media thickness and endothelial dysfunction, 34–36 modifies the circadian activity of the sympathetic system, 37 and regulates glucose metabolism 38,39 . However, IGF‐I also has vasorelaxation and protective effects on the vascular system, inducing nitric oxide 1,2 and elastin synthesis, 40 interacting with vascular smooth cell potassium channels 41 and preventing apoptosis of these cells 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correlation between GH/IGF‐I values and BP values is in agreement with most studies (Kraatz et al ., 1990; Ezzat et al ., 1994; Minniti et al ., 1998b; Colao et al . 2000), although higher GH values were found in hypertensive acromegalics in a single report (Ikeda et al ., 1993). Neither did the appearent duration of disease, which has been reported to contribute to myocardial performance impairement in acromegalics (Colao et al ., 1999), correlate with either BP values or glucose tolerance in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting BG and IRI have been reported to be higher in acromegalics than in nonacromegalic subjects, but similar in normotensive and hypertensive acromegalics (Ezzat et al ., 1994). Post‐load IRI values have been correlated with clinical BP values in a single small series of acromegalics (Ikeda et al ., 1993). In the present study, neither fasting nor postload IRI was found to differ between hypertensive and nonhypertensive patients (data not‐shown), and IRI tended to correlate with the degree of glucose tolerance abnormalities but not with BP values.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on acromegaly using traditional RIA (33,34) have demonstrated an association between insulin and hypertension. In our study this association was not found.…”
Section: Discussionmentioning
confidence: 98%